68Ga‐PSMA PET/CT for the detection of bone metastases in prostate cancer: a systematic review of the published literature. (29th October 2017) - Zacho, Helle D.; Nielsen, Julie B.; Haberkorn, Uwe; Stenholt, Louise; Petersen, Lars J.
Summary: Background: 68 Ga‐labelled prostate‐specific membrane antigen (PSMA) is a promising PET ligand for the detection of prostate cancer. Little attention has been given to the ability of 68 Ga‐PSMA PET/CT to detect malignant bone lesions and whether this approach is superior to existing bone imaging modalities. Aim: To review the existing data of 68 Ga‐PSMA PET/CT for the diagnosis of bone metastases in prostate cancer. Methods: Systematic review of the peer‐reviewed literature. Results: Among 1858 papers in the original search, 37 papers were included in the analysis (six case reports and 31 case series). The vast majority of the studies were low‐level evidence studies. Most studies presented data on detection rates without a reference standard. All but two studies were of a retrospective nature. Several cohort studies showed bone metastasis in 5–60% of patients with prostate cancer, including in patients with very low‐PSA values. For primary staging, 68 Ga‐PSMA PET/CT outperformed bone scans, while the superiority of 68 Ga‐PSMA PET/CT compared with bone scans with respect to biochemical recurrence and metastatic castration‐resistant prostate cancer (mCRPC) remains to be demonstrated. Conclusion: 68 Ga‐PSMA PET/CT has shown to be a promising technique for use in prostate cancer. 68 Ga‐PSMA PET/CT shows more lesions than bone scans, but data on diagnostic performance are very limited and indicate improved diagnostic performance in primary staging but not in mCRPC. Properly designed studies are needed to clarify the diagnostic performance of 68 Ga‐PSMA PET/CT as well as its superiority over existing methods before 68 Ga‐PSMA PET/CT can be routinely used for bone imaging.